NOBLE GASES IN ORTHOPYROXENITE ALH84001: A DIFFERENT KIND OF MARTIAN METEORITE WITH AN ATMOSPHERIC SIGNATURE - Swindle T.D.; Grier J.A.; Burkland M.K. (My University, 1995)
Meteorite ALH84001, a recently identified martian orthopyroxenite, has xenon with higher ratios of 129Xe/132Xe (up to 2.15) than any previously identified martian sample except the glass in EETA 79001, suggesting that it has incorporated a relatively large amount of martian atmosphere. As such, it should be a fruitful sample to study in order to try to determine incorporation mechanisms, but it is petrogenetically very different from other martian meteorites with similar noble gas signatures. We determine a cosmic-ray exposure age of 15.8 +/- 1.6 Ma, longer than any other martian meteorites, requiring either another impact event on Mars, or another breakup of a martian fragment en route to Earth. Argon systematics suggest an age much older than the other martian meteorites and may indicate a substantial amount of martian atmospheric argon as well. Excesses of 80Kr and 82Kr in one sample are consistent with neutron capture on bromine in situ, but not with an atmosphere rich in Br-derived isotopes.